Memory and metacognition: towards a minimalist conception of episodic memory attributable to non-linguistic animals - Corda, Gabriel (Analysis. Journal of Philosophical Research, 2022)
Episodic memory has been considered a capacity only possessed by humans beings because it requires sophisticated and complex cognitive skills such as metacognition or a narrative structure (Klein and Nichols, 2012; Keven, 2015; Mahr and Csibra, 2018), or because it relies on phenomenological features that non-linguistic beings are not able to manifest (Tulving 1999, 2005; Klein 2013). The present article offers arguments against both theses. It claims that the first one confuses the epistemic and the empirical sense of remembering (Craver, 2020) and that it is possible to uphold a legitimate notion of episodic memory based on the empirical sense. The second does not consider the existence of effective methods to differentiate semantic and episodic traits in humans, according to which certain contents of episodic memories are not usually encoded by semantic memory. Taking this contents in account, a criterion is offered for attributing episodic memory in empirical sense.